Let the partial trace $\mathrm{tr}_B$ be a mapping from an endomorphism End$\left( H_A\otimes H_B \right)$ onto an endomorphism End$\left( H_A \right)$. Then the partial trace is defined as

$$ \mathrm{tr}_B:\; S\otimes T \mapsto \mathrm{tr}(T)S $$

with $S\in$ End$\left( H_A \right)$ and $T\in$ End$\left( H_B \right)$. Now it is stated that the partial trace commutes with (left and right) multiplication of an operator $T_A \otimes \mathrm{id}_B$ with $T_A\in$ End$\left( H_A \right)$ and $S_{AB}\in$ End$\left( H_A\otimes H_B \right)$ such that

$$ \mathrm{tr}_B\left( S_{AB} \left(T_A \otimes \mathrm{id}_B \right) \right)=\mathrm{tr}_B\left( S_{AB} \right)T_A. $$

Here, I am not quite sure what is happening. I would expect, that there should appear the dimension of B, so

$$ \mathrm{tr}_B\left(T_A \otimes \mathrm{id}_B\right)= \mathrm{dim}_B T_A. $$

Intuitively, I see that the operator does only act non-trivially on End$\left( H_A \right)$ therefore the result looks reasonable. However, I am somewhat not able to express this mathematically.


Note that $S_{AB}$ can be expressed in the form $$ S_{AB} = \sum_{k=1}^N S_A^{(k)} \otimes S_B^{(k)} $$ for some operators $S_A^{(k)},S_B^{(k)}$ (we could be a bit more specific, but this will do). We then have $$ \operatorname{tr}_B(S_{AB} (T_A \otimes \operatorname{id}_B)) = \\ \operatorname{tr}_B\left(\sum_{k=1}^N (S_A^{(k)} \otimes S_B^{(k)}) (T_A \otimes \operatorname{id}_B)\right) =\\ \sum_{k=1}^N\operatorname{tr}_B\left( (S_A^{(k)} \otimes S_B^{(k)}) (T_A \otimes \operatorname{id}_B)\right) = \\ \sum_{k=1}^N\operatorname{tr}_B\left( (S_A^{(k)} T_A) \otimes S_B^{(k)} \right) = \\ \sum_{k=1}^N \operatorname{tr}(S_B^{(k)})S_A^{(k)} T_A =\\ \left(\sum_{k=1}^N \operatorname{tr}(S_B^{(k)})S_A^{(k)}\right) T_A =\\ \operatorname{tr}_B(S_{AB}) T_A $$ as desired.


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.